2019
DOI: 10.3390/en12122271
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Renewable Sources of Electricity in the Context of Sustainable Development of the New EU Member States

Abstract: Climate change and awareness of the need to care for the environment have resulted in a global increase in the interest in renewable energy sources. The European Union (EU) is active in this respect and requires Member States to fulfill specific plans in the transformation of their energy systems. We employed hierarchical cluster analysis in an attempt to distinguish those countries among the new EU Member States that increased their electrical capacity from renewable energy sources to the greatest extent whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 80 publications
0
11
0
1
Order By: Relevance
“…Various research methods are also shown in studies on sustainable energy development, including multivariate statistical methods and clustering or rank-based methods. A study by [63] uses the Ward's clustering methods to distinguish groups of countries in terms of the energy potential of RES in the so-called "New" EU Countries. The analysis concerned the comparison of 2004 and 2016.…”
Section: Source Of Indicatormentioning
confidence: 99%
“…Various research methods are also shown in studies on sustainable energy development, including multivariate statistical methods and clustering or rank-based methods. A study by [63] uses the Ward's clustering methods to distinguish groups of countries in terms of the energy potential of RES in the so-called "New" EU Countries. The analysis concerned the comparison of 2004 and 2016.…”
Section: Source Of Indicatormentioning
confidence: 99%
“…In addition, we demonstrate that there is a need for maintaining a proper balance between economic development and environmental protection, which is a must for the EU sustainable energy development agenda and all its accompanying targets for all its Member States.Energies 2020, 13, 965 2 of 20 allows comparing the dynamics of economic development over time and on a cross-country basis but recently one can hardly assess economic growth without attributing attention to the consumption of natural resources and preserving the environment. In was in the past decades that the increasing attention to global warming and climate change has focused on the relationship between environmental pollutants, energy consumption and economic growth [1][2][3]. In order to effectively control greenhouse gas (GHG) emissions and ensure the sustainability of economic development, it is important to better understand the relationships between greenhouse gas emissions, energy consumption and economic growth [4][5][6].…”
mentioning
confidence: 99%
“…The method of protection within each of these areas may be different. A very important activity in relation to Natura 2000 areas is monitoring the status of natural habitats, habitats of plant and animal species and their populations within them, and reporting the results of these observations, as it enables the assessment of the effectiveness of conducted conservation activities [32] In addition, a further limitation has been added from densely populated areas, where investments for wind energy purposes cannot be implemented or encounter significant inconveniences in practice [33][34][35][36].…”
Section: Review Of Energy Policies In Poland Relevant West Pomeranianmentioning
confidence: 99%